Franz Liszt and the Birth of Modern Musical Institutions: The reception of Franz Liszt in Danish musical life, 1839–1928 - Nissen, Peter E. (Danish Yearbook of Musicology, 2007)
Research on the reception of Franz Liszt in Danish musical life between 1839 and 1928 shows how Liszt’s music was received in various ways due to factors such as the kind of audience, the genre, and the venue of the concerts. Turbulence and controversy arose from Liszt’s visit in Copenhagen in 1841, and continued during the introduction of his works over the following years. Liszt was associated with French modern art, and was treated with suspicion among conservative Kenner in the local music society Musikforeningen, which leaned heavily on ideals derived from the Gewandhaus music society in Leipzig. On the other hand, Liszt was received with enthusiasm among the rising middle-class audience (Liebhaber), and used in propaganda by liberal democrats in the years leading up to the introduction of the democratic constitution of the Danish monarchy. In the 1870s, the operas of Richard Wagner helped pave the way for a breakthrough for Liszt’s music in Denmark, but in contrast to Wagner’s operas it was difficult for Liszt’s works to maintain this foothold. An essential reason for this was the fact that while Wagner worked within the genre of opera, Liszt tried to modernize the symphonic genre – through his symphonic poems – within a hostile philharmonic culture. In addition, his church music was well received in the late nineteenth century. In the early twentieth century, neither his piano works, his symphonic poems, nor his church music remained a part of the established repertoire.